(untitled) (Editora Impacto Científico, 2025)
Carbohydrate-rich supplements are widely used by athletes due to the rapid energy they provide during sports practice. Among these, gels stand out for their ease of consumption and high concentration of carbohydrates in small portions. This study reviews information on gel-based dietary supplements, addressing their composition, main ingredients, current regulations, and research related to their development. DOI: https://doi.org/10.56238/edimpacto2025.090-043